Existence and Global Asymptotic Behavior of S-Asymptotically ω-Periodic Solutions for Evolution Equation with Delay. (19th November 2020) - Qiao, Hong; Li, Qiang; Yuan, Tianjiao
Abstract : This paper is concerned with the abstract evolution equation with delay. Firstly, we establish some sufficient conditions to ensure the existence results for the S -asymptotically periodic solutions by means of the compact semigroup. Secondly, we consider the global asymptotic behavior of the delayed evolution equation by using the Gronwall-Bellman integral inequality involving delay. These results improve and generalize the recent conclusions on this topic. Finally, we give an example to exhibit the practicability of our abstract results.